Peran Guru Bimbingan Dan Konseling Dalam Membentuk Karakter Mandiri Siswa Dalam Adegan Pendidikan - Juwanto, Juwanto; Taufiq, Agus; Yustiana, Yusi Riksa (Universitas Nusantara PGRI Kediri, 2023)
This article aims to describe the role of education in shaping student independence. Education as the spearhead in developing the quality of Human Resources has an important role in developing and improving the quality of a country. The quality of education is not only measured in the academic component but how can guarantee the development of independent students in accordance with the stages of development where one of the main components is student character. This article uses a literature review approach, namely selecting specific sources according to the theme, identifying articles, and then compiling articles. Meanwhile, the data collection technique used is through journals, books, and articles, both national and international, which are related to the subject matter that is the theme of this article. In order to support the study, a small survey was conducted at the school, namely SMA I Lembang Bandung. Education is carried out with the aim of forming not only the academic component of students but also delivering students to be independent as a whole. In forming the independent character of students, it is necessary to have parties who have responsibility and authority such as teachers, parents, and the community. On the other hand, cultural factors which are an integral component of the community structure cannot be separated from influencing the character development factors of independent students. Thus it is necessary to have synergy in building quality Human Resources (HR).